(untitled) (Tempo e Argumento, 2011)
This article presents a brief discussion about the deep changes to the notion of citizenship in modernity and post-modernity, both in the light of post-colonial critique and the political challenges posed by these changes. Critical emphasis is placed on the use of the mechanisms that grant citizenship as a mean of integrating migrants within Europe.